Redefinisi Kosakata Terkait Perang Bahasa (Kajian Linguistik Forensik) - Ali Kusno (Universitas Mulawarman, 2021)
The purpose of this study is to formulate a redefinition of vocabulary related to language wars. This study uses descriptive qualitative research methods. The data analysis technique uses an interactive model consisting of three analysis components: data reduction, data presentation, and drawing conclusions or verification. The activities of the three components are carried out in an interactive form with the data collection process. The rise of legal cases related to language is in line with the increasingly massive use of social media in society. These cases are part of the language war. Society, in general, is still common and even misunderstands related speech that is categorized as language war and has the potential to be caught in the law. Language war is the use of the language of a speaker/writer intentionally as a tool/weapon for self or group interests. Language wars are carried out directly or indirectly that attack the ideas, thoughts, behaviour, honour, or physical condition of a person or group of speech partners. Language wars include suggestions, criticism, ridicule, incitement, defamation, insults, and slander. More detailed definitions and socialization efforts to the public regarding various language criteria are preventive measures for various legal cases related to language.